2020
DOI: 10.11604/pamj.2020.37.319.26267
|View full text |Cite
|
Sign up to set email alerts
|

Clinical stage I synchronous bilateral testicular germ cell tumor with different histopathology: a case report

Abstract: Bilateral testicular germ cell tumors (BTGCT) occur in 1 to 4% of patients with testicular cancer and of these, 10-15% are synchronous. Overall, BTGCT represents less than 0.5% of all new cases of testicular cancer. There are few reports in the literature of synchronous BTGCT with different histology. We present the case of a 30-year-old man who presented to our genitourinary tumor unit with a bilateral increase of testicular volume. After initial assessment, a testicular ultrasound showed the presence of soli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Published case reports or case series reporting survival rates and follow up reports of patients with synchronous GCTC with different histopathology are scarce. Two case reports of earlier stages of synchronous GCTC with different histopathology showed no recurrences after 1–2 years of follow up [10] , [17] . Follow up should include physical examination, serum marker measurement, chest radiography, scrotal USG and CT abdomen [15] .…”
Section: Clinical Discussionmentioning
confidence: 96%
“…Published case reports or case series reporting survival rates and follow up reports of patients with synchronous GCTC with different histopathology are scarce. Two case reports of earlier stages of synchronous GCTC with different histopathology showed no recurrences after 1–2 years of follow up [10] , [17] . Follow up should include physical examination, serum marker measurement, chest radiography, scrotal USG and CT abdomen [15] .…”
Section: Clinical Discussionmentioning
confidence: 96%
“…11 In 2015, the 49th case report was published by Anastasiou et al 6 Since then, we found only seven cases by searching the PubMed's and Google Scholar's databases. 2,3,10,[12][13][14][15] Therefore, our case is the 57th synchronous bilateral testicular tumor case with different histology to have been reported up to date, according to PubMed's and Google Scholar's databases.…”
Section: Discussionmentioning
confidence: 99%
“… 9 Although rare, different histological types of synchronous tumors have been reported. 10 The first case of bilateral testicular tumors with different histological types was reported by Coleman et al in 1954. 6 In 2003, Coli et al reported the 43rd case of bilateral testicular tumors with different histological types.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the infrequency of this condition, the treatment approach followed is the standard management of unilateral testicular carcinoma, with the additional consideration of prioritizing the more aggressive tumor component [ 12 , 13 ]. Salazar-Mejia et al reported that their patient’s poor compliance with surveillance was identified as a risk factor for relapse and poor outcome; the patient underwent one cycle of bleomycin, etoposide, and cisplatin (BEP) for adjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Salazar-Mejia et al reported that their patient’s poor compliance with surveillance was identified as a risk factor for relapse and poor outcome; the patient underwent one cycle of bleomycin, etoposide, and cisplatin (BEP) for adjuvant chemotherapy. After four years of follow-up, their patient showed no evidence of relapse [ 13 ]. Collaboration among urologists, pathologists, radiologists, oncologists, and support services is essential for optimal patient outcomes in the management of testicular tumors.…”
Section: Discussionmentioning
confidence: 99%